Inovasi Bahan Ajar dalam Implementasi Kurikulum Merdeka di SMAN 1 Tinambung : Pengabdian - Sufyan Hakim; Aslam, Muhammad; Yunus, Muh. (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program aimed to enhance teachers' capacity to develop innovative teaching materials aligned with the principles and requirements of the Merdeka Curriculum at SMAN 1 Tinambung. The activity was carried out for three months, from April to June 2024, involving 29 teachers as participants. The implementation methods consisted of interactive training, teaching material development workshops, intensive mentoring, and continuous evaluation. Evaluation results from questionnaires indicated that: (1) the presented materials were deemed highly relevant to the needs of Merdeka Curriculum implementation; (2) the activity significantly improved participants' understanding and skills in creating innovative teaching materials; and (3) the interactive training methods and intensive mentoring model were highly appreciated by all participants. This program successfully empowered teachers to develop contextual and creative teaching materials, which is expected to encourage an improvement in the quality of learning at the school.